Photocatalytic Activity of ZnxMn3−xO4 Oxides and ZnO Prepared From Spent Alkaline Batteries - Alcaraz, Lorena; Jiménez-Relinque, Eva; Plaza, Lorenzo; García-Díaz, Irene; Castellote, Marta; López, Félix A. (Frontiers in Chemistry, 2020)
Oxides with ZnxMn3−xO4 stoichiometries and ZnO were synthesized from the “black mass” material recovered from spent alkaline batteries. The oxides were characterized by XRF, XRD with Rietveld refinement, SEM, and TEM methods. Optical characterization included diffuse reflectance (DRS) and photoluminescence (PL) measurements. ZnO presented a clear band edge in the UV region, and PL signals were detected. The Zn/Mn oxides showed strong absorption in the UV region and a continuous absorption band in the Vis-IR regions. There is a non-detected PL signal due to excited charges being trapped on sub-band energy states and/or transfer by non-radiative paths. Photocatalytic activity under both irradiation conditions was evaluated using the resazurin dye test, terephthalic acid fluorescence probe method, and NOx air purification evaluation. In the three photoactivity tests, ZnO performed well under both UV and Vis irradiation, whereas no evidence of any appreciable photocatalytic activity was observed for the Zn/Mn oxides. The results are discussed in terms of the findings of previously reported optical measurements.